Architectural fragments with intricately carved with human figures - Temples of India Project Team (Jio Institute, 2024)
The beam, intricately carved with human figures, likely adorned the varandika of the temple, the adjoining portions between the temple walls and the spire. The protruding offsets typically portray mithuna figures within the niches, while the recess between the two offsets is exquisitely carved with images of apsaras or women engaged in different actions. The male figures are often depicted wielding weapons and in the company of female companions.